2022
DOI: 10.21931/rb/2022.07.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metal Pollution in the Blood Serum of Industrial Workers, Mosul, Iraq

Abstract: The study was conducted in the two main industrial areas in Mosul, northern Iraq, where the study included measuring the number of heavy metals (cadmium, aluminum, mercury, chromium) in the blood of workers in those areas. For 20 workers, in contrast, blood samples were drawn from Mosul University employees. They were considered as a control group for being far from industrial activity and for 20 employees. An atomic absorption device was used to analyze blood samples after diluting. In addition, workers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Many studies have shown an increase or rise in ALP enzyme levels in the blood serum of HFpEF patients 17,19,25 . People with liver diseases related to heart failure are often not symp-tomatic for prolonged periods and are accompanied by a defect in liver enzymes or abnormal levels, which is the first sign of liver disease [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown an increase or rise in ALP enzyme levels in the blood serum of HFpEF patients 17,19,25 . People with liver diseases related to heart failure are often not symp-tomatic for prolonged periods and are accompanied by a defect in liver enzymes or abnormal levels, which is the first sign of liver disease [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…And that the benefits have a stronger influence than the self-efficacy dimension through the relative change test, so this was in a positive direction. A study conducted before 26,27 indicated that the greater the effect of the activity and the benefits, the greater the feeling of change, and the greater the perceived benefits among the people participating in the study. There is a direct correlation relationship, but it is significant between (Self-efficacy) and each of (Social support) and (activity-related affect) as a function of the value of the correlation coefficient whose value appeared equal to (0.781) and (0.878)", and this relationship is significant which p-value appeared equal to (0.000) and (0.000), respectively, which are less than (0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The Study [13] indicates that industrial workers are at risk of imminent death Because of the high concentrations of heavy metals, which are considered industrial pollutants They are exposed to it, and this requires a quick and urgent intervention from all health and environmental aspects to protect them. As a study [14] showed The five chimneys in the Kirkuk Cement Factory contribute to the high rates of air pollution in very high quantities, causing damage to housing, agricultural lands and personnel working inside and outside the plant, due to the amount of plankton and dust that the chimneys emit in the nearby areas, Which is arable land that works to destroy and kill the plantations and reduce the life of the trees in the area, and causes great damage to human health in general.…”
Section: Introductionmentioning
confidence: 99%